2022
DOI: 10.1109/jsen.2022.3210699
|View full text |Cite
|
Sign up to set email alerts
|

A Retail Object Classification Method Using Multiple Cameras for Vision-Based Unmanned Kiosks

Abstract: Several unmanned retail stores have been introduced with the development of sensors, wireless communication, and computer vision technologies. A vision-based kiosk that is only equipped with a vision sensor has significant advantages such as compactness and low implementation cost. Using convolutional neural network (CNN)-based object detectors, the kiosk recognizes an object when a customer picks up a product. In retail object recognition, the key challenge is the limited number of detections and high intercl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…In addition to being applied to augmented reality, sensors are combined with intelligent algorithms for reliable target recognition. Li et al [4] combined a hybrid tactile sensor with a robot and analyzed the tactile information feedback from the sensor through machine learning to achieve object recognition; Jeon et al [5] combined visual sensors with convolutional neural networks to achieve classification of retail products, solving the problem of similarity between classes; Chen et al [6] implemented heterogeneous fusion of LiDAR and visual sensors, combined with deep learning, to achieve obstacle detection and distance measurement in front of vehicles.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to being applied to augmented reality, sensors are combined with intelligent algorithms for reliable target recognition. Li et al [4] combined a hybrid tactile sensor with a robot and analyzed the tactile information feedback from the sensor through machine learning to achieve object recognition; Jeon et al [5] combined visual sensors with convolutional neural networks to achieve classification of retail products, solving the problem of similarity between classes; Chen et al [6] implemented heterogeneous fusion of LiDAR and visual sensors, combined with deep learning, to achieve obstacle detection and distance measurement in front of vehicles.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Sinha et al [ 11 ] demonstrated that the registration process can be easily completed by patients or their proxies using kiosks. However, unlike unmanned retail stores [ 12 ], there is no evidence that the use of kiosks can completely replace human-based triage (ie, triage nurses). Without proper control, full self-triage could lead to disparities.…”
Section: Introductionmentioning
confidence: 99%